Textationships: an exploratory qualitative study of intimate text-based relationships - Smith, Jennifer Ann (Kansas State University, 2021)
This qualitative, exploratory study examines how people use communication technology to develop new forms of intimate romantic relationships called Textationships. For the first time in human history, individuals are able to transmit billions of bits of text between people around the world. Text communication has morphed beyond its original informational uses; it now includes deeply personal exchanges. Utilizing a collective case study design, a diverse sample of 6 middle-aged women engaged in text-only relationships were interviewed using a semi-structured open-ended questionnaire. Following a pilot phase to enhance its reliability and content validity, the final questionnaire targeted three key domains guiding research – context, intimacy, and motivation. Thematic coding of their narrative responses by two experienced coders was conducted. Several themes were reliably derived within each of the relationship domains. Within-case analyses revealed that the participants achieved high levels of intimacy and interdependence in their Textationships. Between-case themes included avoidance, secrecy, investment, interdependence, online disinhibition and issues of distance. Discussion of research implications and specific suggestions for future research are presented.
Keywords: Computer mediated communications; Computer mediated intimate relationships; Electronic mediated communicationsTextationships